Feasibility of low-dose contrast media in run-off CT angiography on dual-layer spectral detector CT - Ren, Haiyan (Quant Imaging Med Surg, 2021)
BACKGROUND: The aim of the present study was to assess the feasibility of applying low-dose contrast media (CM), and to explore the optimal virtual monoenergetic images (VMIs) in run-off computed tomography (CT) angiography (CTA) on dual-layer spectral detector CT (SDCT). METHODS: Forty patients were randomly assigned into a control group using routine volume CM (group A) and an experimental group using half-volume CM (group B). In groups A and B, 120 kVp polychromatic conventional images were generated via hybrid iterative reconstruction algorithm defined as A1 and B1, respectively. Additionally, in group B, VMIs (range, 40–120 keV) were reconstructed via a spectral reconstruction algorithm defined as B2–B10. Vascular attenuation, noise, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and radiation dose were evaluated. Subjective evaluation was performed using a 5-point scale. RESULTS: The patient demographics and radiation dose demonstrated no significant difference between groups A and B [dose length product (DLP): 1,823.45±512.68 vs. 2,014.40±453.25 mGy·cm, P=0.229; volume CT dose index: 14.92±3.40 vs. 16.26±2.85 mGy, P=0.208; the effective dose (ED): 10.82±3.02 vs. 11.88±2.67 mSv, P=0.229]. The mean vascular attenuation was higher in group B2 (40 keV) and was lower in group B3 (50 keV) in comparison with that in group A1 (487.07±154.21 vs. 414.35±71.66 HU, 329.90±100.25 vs. 414.35±71.66 HU, P>0.05). Compared with group A1, the mean noise was similar in group B2 (40 keV) and was lower in group B1 and groups B3–B10 (50–120 keV) (14.81±5.67 vs. 17.29±4.70 HU, P>0.05; 6.75±1.23–11.26±3.24 vs. 17.29±4.70 HU, P<0.05). The mean SNR and CNR in group B2 (40 keV), as well as the mean SNR in group B3 (50 keV), were significantly higher than those of group A1 (38.21±7.52 vs. 28.25±7.20, 32.70±7.79 vs. 24.54±6.60, 32.85±7.10 vs. 28.25±7.20, P<0.05), and the mean CNR in group B3 (50 keV) was similar to that in group A1 (26.66±7.32 vs. 24.54±6.60, P>0.05). Scores of subjective image quality (IQ) in group B2 (40 keV) and B3 (50 keV) were similar to those in group A1 {5 [4.25, 5] vs. 5 [4, 5], 5 [5, 5] vs. 5 [4, 5], P>0.05}, and showed a declining trend in group B4 (60 keV) {4 [4, 5] vs. 5 [4, 5], P>0.05}. CONCLUSIONS: It is feasible to perform run-off CTA using low-dose CM with VMI on SDCT. The VMIs at 40–50 keV were the optimal choice and did not compromise IQ.